2018
DOI: 10.1002/cncy.22034
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnostic precision of urine cytology by implementation of The Paris System and the use of cell blocks

Abstract: In support of the new TPS recommendations, the application of stringent "TPS-like" and TPS criteria improves the value of an AUC diagnosis for clinicians and patients by lowering the AUC rate and increasing the positive predictive value of AUC for high-grade urothelial carcinoma. CBs can be used to help resolve problematic cases for more definitive diagnostic categorization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 21 publications
(36 reference statements)
2
39
0
Order By: Relevance
“…Accordingly, other cytological specimens such as thyroid fine needle aspiration and urine have indeed witnessed a drop in the atypical rate after the broad implementation of terminology systems, with improved overall test performance. [15][16][17] The most common primary site of malignancy in males with pleural effusion was the lung, in agreement with the most recent literature. 18,19 Among women, carcinomas of the breast were the most common epithelial neoplasm, also in accordance with previ- is also a useful marker for the distinction between epithelial and mesothelial lineage and together with Ber-EP4 may serve as a limited yet informative panel for the difficult question of cell origin.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Accordingly, other cytological specimens such as thyroid fine needle aspiration and urine have indeed witnessed a drop in the atypical rate after the broad implementation of terminology systems, with improved overall test performance. [15][16][17] The most common primary site of malignancy in males with pleural effusion was the lung, in agreement with the most recent literature. 18,19 Among women, carcinomas of the breast were the most common epithelial neoplasm, also in accordance with previ- is also a useful marker for the distinction between epithelial and mesothelial lineage and together with Ber-EP4 may serve as a limited yet informative panel for the difficult question of cell origin.…”
Section: Discussionsupporting
confidence: 89%
“…Future studies adopting criteria developed by this international expert community are warranted to evaluate any impact. Accordingly, other cytological specimens such as thyroid fine needle aspiration and urine have indeed witnessed a drop in the atypical rate after the broad implementation of terminology systems, with improved overall test performance …”
Section: Discussionmentioning
confidence: 99%
“…Northrup et al also showed the rate of AUC reduced from 18.5% to 26.5% with TPS, where 47.4% of AUC cases were reclassified into NHGUC and 2.9% of them upgraded to SHGUC . Chan et al study also showed TPS criteria improves the value of an AUC diagnosis by lowering the AUC rate and increasing the positive predictive value of AUC diagnosis for high‐grade urothelial carcinoma. However, in the study of Granados et al, there was an increase in the AUC category .…”
Section: Discussionmentioning
confidence: 95%
“…8 So far, several studies have assessed the efficacy of TPS in urine cytology evaluations, in most of which TPS has been introduced as a reporting urine cytology template which has increased the detection rate of HGUC and reduced the rate of equivocal diagnoses. [9][10][11] In one study by Cowan et al, 40% of the cases with confusing diagnosis were reclassified into a higher risk category, while 25% of the cases with positive HGUC were categorized into a lower risk group using TPS criteria. 12 In another study, the frequency of AUC cases declined, and their rate was associated with a subsequent histological diagnosis of increased HGUC.…”
mentioning
confidence: 99%
“…The most significant decreases in AUC rates were seen in institutions with previous high AUC rates. In addition, publications on adoption of the Paris system not only indicate a decrease in the rates of AUC, but also improvements in the specificity of AUC for the detection of HGUC 20 …”
Section: Strengthsmentioning
confidence: 99%